Treatment Outcomes in Very High-risk Prostate Cancer Treated by Dose-escalated and Combined-Modality Radiation Therapy. (April 2016) - Shilkrut, Mark; McLaughlin, Patrick W.; Merrick, Gregory S.; Vainshtein, Jeffrey M.; Hamstra, Daniel A.
Abstract : Objectives: The aim of this study was to report treatment outcomes in patients with very high-risk prostate cancer (VHRPC) treated with dose-escalated radiotherapy. Methods: We conducted a retrospective multi-institutional review on patients with VHRPC (those with at least 2 high-risk factors of prostate-specific antigen >20 ng/mL, Gleason score 8 to 10, or clinical T3 to T4 stage), treated with either dose-escalated external-beam radiotherapy (EBRT) or combined-modality radiotherapy (CMRT) consisting of pelvic irradiation and permanent interstitial brachytherapy. Results: A total of 238 patients with VHRPC were identified. Of them, 69% of patients received EBRT and 31% received CMRT; 88% received androgen-deprivation therapy (ADT), 56% for ≥24 months (long-term ADT). The majority (69%) of patients were above 65 years old and were less likely to receive CMRT than younger patients (25% vs. 43%, P =0.006), although they did not differ from younger patients in tumor characteristics. Median follow-up was 61 months (interquartile range, 38 to 93 mo). Biochemical progression-free survival (BPFS), distant metastasis-free survival (DMFS), and cancer-specific survival (CSS) for all patients at 8 years were (±SE): 50.6%±4.7%, 68.5%±4.3%, 78.7%±3.8%, respectively, and were similar for patients 65 years and below versus above 65 years old (BPFS: HR=0.88, P =0.56; DMFS: HR=0.79, P =0.40; CSS HR=0.99, P =0.99). After adjustment for patient, tumor, and treatment-related covariates on multivariate analysis, CMRT was associated with improved BPFS (HR=0.44, P =0.012) with trends for DMFS (HR=0.52, P =0.10) and CSS (HR=0.55, P =0.21), whereas long-term ADT was independently associated with improved BPFS (HR=0.40, P =0.019), CSS (HR=0.20, P =0.002), and PCSM (HR=0.25, P =0.004). Conclusions: Dose-escalated EBRT or CMRT with long-term ADT resulted in favorable clinical outcomes for patients with VHRPC. Abstract : Supplemental Digital Content is available in the text.